2005
DOI: 10.4049/jimmunol.174.5.2661
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of a New ARTC1 Peptide Ligand Uniquely Expressed in Tumor Cells by Antigen-Specific CD4+ Regulatory T Cells

Abstract: CD4+ regulatory T (Treg) cells play an important role in the maintenance of immunological self-tolerance by suppressing immune responses against autoimmune diseases and cancer. Yet very little is known about the natural antigenic ligands that preferentially activate CD4+ Treg cells. Here we report the establishment of tumor-specific CD4+ Treg cell clones from tumor-infiltrating lymphocytes (TILs) of cancer patients, and the identification of an Ag recognized by Treg cells (ARTC1) gene encoding a peptide ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(97 citation statements)
references
References 52 publications
4
89
1
3
Order By: Relevance
“…The first group includes Tregs that act in a cell-to-cell contact-mediated fashion as is the case for CGA-specific Tregs identified in the current study (12,13). In contrast, another group of human TA-specific Tregs like WT-1-specific and EBNA1-specific Tregs appear to act in a soluble factor-dependent fashion (14,41).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The first group includes Tregs that act in a cell-to-cell contact-mediated fashion as is the case for CGA-specific Tregs identified in the current study (12,13). In contrast, another group of human TA-specific Tregs like WT-1-specific and EBNA1-specific Tregs appear to act in a soluble factor-dependent fashion (14,41).…”
Section: Discussionmentioning
confidence: 75%
“…However, the identity of these Ags remains largely unknown. One major finding was the identification of TAderived epitopes encoded by two cancer-germline Ags (CGAs), LAGE-1 and ARTC1, that were recognized by human TA-specific Tregs isolated from TILs of melanoma patients (12,13). Most recently, the Wilm's TA overexpressed by leukemias was shown to stimulate TA-specific Treg clones generated in vitro from PBLs of normal donors (14).…”
mentioning
confidence: 99%
“…Wang et al were the first to isolate human tumor-associated antigen (TAA)-specific Tregs, in particular Tregs that were specific for the cancer/testis antigen LAGE1 among the TILs of melanoma patients [83]. One year later, the same authors identified Tregs that specifically recognized the ARTC-1 peptide [84]. Another group has successfully detected-again in melanoma patients-circulating Tregs that were specific for multiple distinct melanoma-associated antigens including the glycoprotein 100 (gp100), tyrosinase-related protein 1 (TRP1), the cancer/testis antigen NY-ESO-1 and the anti-apoptotic protein survivin [85].…”
Section: Specificity Of Tregsmentioning
confidence: 99%
“…Although other types of suppressive cell have been identified, most regulatory T cells are characterized by expression of surface CD25 and by intracellular FOXP3, a transcription factor that mediates many of their inhibitory capabilities (Fontenot et al, 2005). It is unclear what proportion of Tregs react with specificity to tumour antigens (Wang et al, 2005), or whether they are recruited through the recognition of shared self-antigens that are co-expressed by tumour cells (Nishikawa et al, 2003;Darrasse-Jeze et al, 2009). Tregs can inhibit effector T-cell responses during both the induction (Darrasse-Jeze et al, 2009) and the effector stages (Huehn et al, 2004;Sarween et al, 2004) by a number of mechanisms, such as through direct ligation of CTLA-4 with CD80 or CD86 on effector T cells, by promoting the development of inhibitory DCs, or through the generation of inhibitory cytokines, transforming growth factor-b and IL10 (von Boehmer, 2005).…”
Section: Suppression By Regulatory T Cellsmentioning
confidence: 99%